Factor-based LEACH (FLEACH) protocol for extending Wireless Sensor Networks' lifetime - Ahmed, Amodu Oluwatosin (2016)
The improvement of sensor networks’ lifetime has been a major research challenge in recent years. This is because sensor nodes are battery powered and may be difficult to replace when deployed. Low Energy Adaptive Clustering Hierarchical (LEACH) routing protocol was proposed to prolong sensor nodes’ lifetime by dividing the network into clusters. In each cluster, a cluster head (CH) node receives and aggregates data from other nodes. However, CH nodes in LEACH are randomly elected which leads to a rapid loss of network energy. This energy loss occurs when the CH has a low energy level or when it is far from the BS. LEACH with Two Level Cluster Head (LEACH-TLCH) protocol deploys a secondary cluster head (2CH) to relieve the cluster head burden in these circumstances. However, in LEACH-TLCH the optimal distance of CH to BS, and the choicest CH energy level for the 2CH, to be deployed for achieving an optimal network lifetime was not deployed. In this thesis, we have improved on LEACH-TLCH by investigating the conditions set to deploy the 2CH for an optimal network lifetime. We also conduct experiments to indicate how the 2CH impacts on the network at different CH energy levels and (or) CH distance to BS. Our improvement on LEACH-TLCH in this thesis is referred to as Factor-based LEACH (FLEACH) protocol. Investigations in FLEACH shows that as CH gets farther from the BS, the use of a 2CH extends the network lifetime. Similarly, an increased lifetime also results as the CH energy decreases while the 2CH is deployed. The best case considered in FLEACH shows an improvement of over 670% in network lifetime as compared to LEACH-TLCH and improves LEACH by over 700%.